A new species of Clathrosperchonella Lundblad 1937 (Acariformes: Hydrachnidiae: Hydryphantoidea: Rhynchohydracaridae) from Brazil, with descriptions of the female, male and larva - Castro, Luiz Alexandre Simões de [UNESP] (2020)
We describe a new species of the genus Clathrosperchonella, C. olovi sp. nov. from Brazil, including complete information for female, male and larva. This brings the number of named species in the Rhynchohydracaridae to thirteen. In addition, we provide a key to named species of Clathrosperchonella.